Oxytocin Modulation of Zebra Finch Vocal Development - Riffle, Brandy W. (East Carolina University, 2010)
Autism spectrum disorder is associated with deficits in three main behavioral areas: social behaviors, repetitive behaviors, and language abnormalities. Accumulating evidence suggests a potential role for oxytocin signaling in the etiology of autism. Oxytocin signaling is integral to complex social behaviors such as fear, social recognition, and monogamous pair bonding initiation (Wang and Aragona 2004; Kirsch, Esslinger et al. 2005; Choleris, Little et al. 2007). Furthermore, evidence of a causal relationship between altered oxytocin levels and repetitive behaviors exists both humans and animals (Drago, Pederson et al. 1986; Hollander, Novotny et al. 2003). However, limited research exists to document a role for oxytocin and oxytocin related peptides in communication related behavior either in humans or animal models. Oxytocin immunoreactive neurons have been found in brain areas associated with the vocal behaviors of both the mustached bat and the plainfin midshipman fish and increased plasma levels of oxytocin have been linked with the production of sound in humans (Goodson, Evans et al. 2003; Grape, Sandgren et al. 2003; Prasada Rao and Kanwal 2004). Since song birds learn a form of vocal communication, the zebra finch represents a promising animal model for the study of such peptides to determine their role in vocal learning and development and for evaluating effects of exogenously administrated oxytocin on vocal development. As an avian species, zebra finches utilize mesotocin rather than oxytocin signaling (these nonapeptides differ by a single amino acid). Since previous studies suggest a feasible role for oxytocin related peptides in vocal development we developed the following hypotheses: 1) that the mesotocin receptor is distributed in song regions within the male zebra finch brain responsible for both the production of and the learning of song; 2) that the early exposure to peripheral oxytocin would alter normal male zebra finch vocal development; 3) the alteration of zebra finch vocal development would be associated with a decrease in mesotocin receptors within song regions that persists until adulthood. Specific aim 1 was to determine the localization of mestocin receptors within the CNS of an adult male zebra finch. Both traditional cloning techniques and the identification of coding sequences in-silico were employed to gain knowledge of the cDNA sequences corresponding to the mRNA encoding of proteins integral to the mesotocin signaling within the zebra finch which allowed for the development of nucleic acid probes and an antibody to study expression of the zebra finch mesotocin receptor. In sections of fixed zebra finch brain tissue, mesotocin receptor expression patterns at various stages of vocal development: 10 days, 25- [auditory learning], 50- [subsong], 75- [plastic song], and 100-days of age [crystallized song] were determined. Expression of the mesotocin receptor was detected within areas associated with either song learning (Area X, lMAN (lateral magnocelluar nucleus of the anterior nidopallium), song production (HVC (used as a proper noun), RA (robust nucleus of the archopallium), or auditory inputs (L2) at 25, 50, 75, and 100 days of age with peak receptor expression occurring at 50 days. In-situ hybridization experiments were also done to assess mesotocin receptor mRNA expression at 25, 50, 75, and 100 days and results indicated significant expression of mesotocin mRNA in the vocal motor song region HVC. This distinct pattern of staining of the mesotocin receptor, which changes as a function of age corresponding to noted periods of vocal learning in brain areas previously determined to be critical for various aspects of song learning and production, suggests a feasible role for mesotocin signaling in either the production of song, in song learning or both. Specific aim 2 was to determine if exposure to exogenous oxytocin could alter vocal development. Nests of zebra finch hatchlings were injected with varying doses of oxytocin on days 5-9 post hatch. Young male birds were allowed to learn a song from an established adult male tutor and their resulting songs were recorded, analyzed, and compared to those of the control treated group. The overall quality of the song learned (as expressed by song stereotypy scores) and mean note duration were significantly decreased as a function of treatment in both oxytocin dose groups (30 µg/kg, 300 µg/kg) when compared to that of the vehicle treated group. Our results clearly show that exogenous peripheral exposure to oxytocin is capable of producing alterations in song learning in the zebra finch and this may be the result of oxytocin effects on song learning and/or the production of song as a form of social communication. Specific aim 3 determined if the exogenous exposure to oxytocin would persistently alter the density of mesotocin receptors within song regions in treated birds when compared to that of the control treated group. No significant difference was found to exist in the mean optical density of mesotocin receptor immunohistochemical staining in the four song regions examined (vocal motor regions HVC and RA, and song learning regions lMAN and Area X) between the vehicle treated control group and the oxytocin treated birds. These findings suggest that the alteration in normal zebra finch vocal development oxytocin is not through a persistent alteration in mesotocin receptor densities in song control regions. In conclusion, we have shown that the oxytocin related peptide mesotocin may be critical to either song learning, the auditory perception of song, or the vocal production of song since its receptors are located in song control regions previously demonstrated to be critical for these functions. Furthermore, we have demonstrated that the peripheral administration of oxytocin to a young zebra finch hatchling is capable of producing an alteration in the production of the final adult song which could be through a dysfunction in one or all of the various processes of song learning (such as the vocalization of song, the auditory perception of song, or the memorization and learning of song) but that this alteration is not by a long term down-regulation of the mesotocin receptor in song control regions. These results highlight a potential relationship between oxytocin exposure and the alteration of vocal development which is a deficit associated with autism spectrum disorders.
Keywords: Child Development Disorders, Pervasive; Oxytocin; Mesotocin; High Vocal Center; Models, Animal; Finches; Songbirds; Auditory Perception; Vocalization, Animal--physiology; Pharmacology; Child Development Disorders, Pervasive